Feasibility of a Serverless Distributed File System Deployed on an Existing Set of Desktop PCs - Bolosky, Bill; Douceur, John (JD); Ely, David; Theimer, Marvin (Proceedings of the international conference on measurement and modeling of computer systems (SIGMETRICS), 2000)
We consider an architecture for a serverless distributed file system that does not assume mutual trust among the client computers. The system provides security, availability, and reliability by distributing multiple encrypted replicas of each file among the client machines. To assess the feasibility of deploying this system on an existing desktop infrastructure, we measure and analyze a large set of client machines in a commercial environment. In particular, we measure and report results on disk usage and content; file activity; and machine uptimes, lifetimes, and loads. We conclude that the measured desktop infrastructure would passably support our proposed system, providing availability on the order of one unfilled file request per user per thousand days.